Kajian Intertekstual Nasihat dalam Kitab Ayyuhal Walad Imam Al-Ghazzali - Lulu Humairah; Mawardi Mawardi; Amiq Amiq (UIN Sunan Gunung Dajti Bandung, 2022)
This research is entitled Advice in the Book of Ayyuhal Walad by Imam Al-Ghazzali (Julia Kristeva Intertextual Semiotics Study). The Book of Ayyuhal Walad by Imam Al-Ghazzali is a literary work in the form of a treatise, namely a letter containing advice given by Imam Al-Ghazzali to his students related to science and charity. The aims of this study are: 1. To find out what texts are referred to by the text of the book of Ayyuhal Walad by Imam Al-Ghazzali. 2. Understanding the relationship in the text of the book Ayyuhal walad with the reference text. 3. Describe the meaning of the message in the text of the book of Ayyuhal walad, along with the reference text. This research uses descriptive analysis method. The technique of collecting data in this study is based on the results of studying and reviewing data sources in the Ayyuhal walad book, the Qur'an and hadith. Then the approach used is Julia Kristeva's semiotic perspective with intertextual theory, namely the new sign system (Text II) → Transposition → Reference sign system (Text I). Based on the analysis, this study shows that there are 39 advices, which include: 39 advices in the book of Ayyuhal walad, 39 verses of the Qur'an, 39 hadiths. Among them contain wise advice that can be used as a guide for humans to become individuals who have noble character.